Reconstruction of Legal Policy in the Juvenile Criminal Justice System Through the Integration of Local Wisdom Values in Indonesia - Ananda Megha Wiedhar Saputri; Adi Sulistiyono; Hartiwiningsih (PT FORMOSA CENDEKIA GLOBAL, 2026)
Children are an integral part of the continuity of a nation and state and serve as the next generation that determines the future of national development. However, rapid social change, economic disparities, and family problems often lead children to engage in deviant behavior, resulting in conflicts with the law. The phenomenon of children in conflict with the law (ABH) remains a complex issue in Indonesia, where the juvenile criminal justice system has not fully integrated the values of local wisdom. This study examines the current legal policy of the juvenile criminal justice system, identifies its weaknesses and implementation problems, and proposes a reconstruction of legal policy through the integration of Indonesian local wisdom values. This normative research employs socio-legal, statutory, conceptual, and case approaches. Secondary data were obtained from primary, secondary, and tertiary legal materials and analyzed qualitatively using a descriptive-analytical method. The findings indicate that the existing juvenile criminal justice system still has weaknesses and requires legal policy reconstruction through the incorporation of local wisdom values in Indonesia.